Kinetika Hidrolisis Selulosa Menjadi Glukosa Pada Limbah Kulit Nanas (Ananas comosus) Menggunakan Enzim Selulase - Annidya, Putri Azmi; Rachmanto, Tuhu Agung; Novembrianto, Rizka (Mahesa Research Center, 2025)
Pineapple peel waste (Ananas comosus) is a source of organic waste with high lignocellulose content that has the potential to be utilized through a bioconversion process into glucose. This study aims to determine the Michaelis–Menten kinetic equation of cellulose hydrolysis into glucose using cellulase enzymes and analyze the effect of substrate concentration (1–5% w/v) and hydrolysis time (60–180 minutes) on the reaction rate. The research stages include delignification using 5% NaOH at 80ºC and enzymatic hydrolysis with 10% cellulase at pH 5 and 50ºC. Glucose levels were measured using a Brix refractometer through a standard glucose solution calibration method. The results showed an increase in glucose concentration over time and substrate concentration, with the highest conversion of 91.5% at 5% substrate. Kinetic analysis using the Michaelis–Menten equation yielded an average reaction rate constant (k) of 0.3328 min⁻¹, with the highest k of 0.3828 min⁻¹ and the highest Michaelis–Menten constant ( ) of 2.357 mg·L⁻¹ at a substrate concentration of 5%. A significant increase in from 0.2403 (1%) to 2.357 (5%) indicates a decrease in enzyme affinity due to substrate saturation. Therefore, a concentration of 5% is considered the optimal condition for the cellulose hydrolysis process, confirming the potential of pineapple peel waste as an efficient substrate source.